(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
This article presents an overview of current concepts regarding hygiene care for patients wearing removable dentures. The main problems that arise from poor hygiene practices are discussed, including microbial colonization, the development of denture stomatitis, and angular stomatitis. Cheilitis and halitosis . Particular attention is paid to the analysis of modern treatment methods and products—mechanical, chemical, and combined—as well as an assessment of their effectiveness in preventing inflammatory complications. It has been shown that optimizing hygiene care requires a comprehensive approach, including regular cleaning of dentures, disinfection with special solutions, the use of ultrasonic technologies, and patient education on personal hygiene. The use of modern enzymatic and oxygen-based cleansers helps break down biofilms and extend the lifespan of orthopedic structures. The results of the review confirm that systematic adherence to hygiene measures significantly reduces the incidence of inflammatory processes in the oral cavity and improves the quality of life of patients using removable dentures.